Study on the Evolution Law of Ablation Characteristic Signals of High-Voltage Cable Buffer Layer Based on Multi-Parameter Analysis - Kang Guo; Zhengping Wang; Zhibo Tian; Qian Li; Siying Wang; Zhenwei Yang; Huimin Guo (IEEE Access)
In recent years, breakdown failures caused by the ablation of the buffer layer in high-voltage cables have occurred frequently, posing a serious threat to the safe operation of the power grid. Moisture content and external pressure are considered key factors influencing the ablation process of the buffer layer. To address this, this paper establishes a simulation experimental platform to investigate the variations in temperature, ultrasound signals, and electrical signals generated during the ablation of the buffer layer under different moisture content and pressure conditions. These signals are collectively referred to as “multi-physical signals,” which can be used to characterize the developmental stages of the ablation process. This study innovatively established a dedicated experimental platform that allows precise control of moisture content (0-20%) and mechanical pressure (0-200g), enabling the synchronous collection and correlational analysis of temperature field distribution, ultrasonic signals, and high-frequency current features. This approach overcomes the limitations of traditional single-parameter detection methods. The experimental results indicate that the thermal effects generated by the concentration of radial currents and the discharge in the gas gaps within the buffer layer are the main reasons for the changes in the signals. Under 0% moisture content conditions, the maximum temperature at the center of the buffer layer reached $336.4~^{° }$ C, while the temperature peak under humid conditions appeared 20 minutes earlier. The amplitudes of the ultrasonic and high-frequency current signals increased by approximately 65% and 70%, respectively, at a moisture content of 20% compared to the dry state. Compared to dry conditions, the buffer layer is more susceptible to electrochemical corrosion with the aluminum sheath under humid conditions, resulting in signal enhancement, along with some small fluctuations in the signals during the process.